Identifying Tax-Setting Responses from Local Fiscal Policy Programs - Valeria Merlo; Andreas Schanbacher; Georg U. Thunecke; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies tax policy interaction among local governments for both mobile and immobile tax bases. We exploit exogenous changes in the local tax setting of German municipalities due to participation in state debt reduction programs to learn about the size, scope and nature of strategic interaction among local governments. Our results suggest strong and significant tax policy responses both in corporate as well as in property tax rates. Our estimates imply response function gradients in the range of 0.3 to 0.7, depending on the type of tax and state. Policy spillovers from property tax rates remain very local, which is consistent with yardstick competition behavior.
Keywords: C21; H71; H73; R59; 330; local public finance; tax competition; yardstick competition; spatial interaction; tax setting; marginal cost of public funds